China’s hop market: development problems - O.Y. Yurkivsky; Y.M. Yurkivsky; L.Y. Yurkivska; Yu.Yu. Moroz; T.M. Ratoshniuk (Економіка, управління та адміністрування)
China’s hop market and its development have a significant impact on China’s beer market. As a world leader in beer production, China pays considerable attention to the production of hops of the appropriate quality and quantity, taking into account international requirements to increase exports in the future. The formation of the hop production infrastructure was carried out in several stages. The current stage is characterized by the presence of both Chinese companies, joint ventures and representative offices of major multinational companies that import hops into the territory of the People’s Republic of China. The number of farms and areas of hop production have been changing over the past 10 years, and the main hop growing areas are Gansu and Xinjiang Autonomous Region. The economic entities grow Chinese varieties of hops, and the main variety in terms of planting area is Tsingtao Flower. Hop cultivation is carried out under the influence of administrative decisions of local authorities of the People’s Republic of China as well as national and global trends in the hop and beer markets. Despite the functioning of world leaders in hop production on the territory of the People’s Republic of China, problematic issues do not allow to improve the quality of grown hops to ensure the domestic market, which requires the import of hops from Germany, the Czech Republic, and the USA.